2001
DOI: 10.1073/pnas.171610498
|View full text |Cite
|
Sign up to set email alerts
|

Variable β-catenin expression in colorectal cancers indicates tumor progression driven by the tumor environment

Abstract: Invasion and dissemination of well-differentiated carcinomas are often associated with loss of epithelial differentiation and gain of mesenchyme-like capabilities of the tumor cells at the invasive front. However, when comparing central areas of primary colorectal carcinomas and corresponding metastases, we again found the same differentiated epithelial growth patterns. These characteristic phenotypic changes were associated with distinct expression patterns of ␤-catenin, the main oncogenic protein in colorect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

71
821
5
12

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 974 publications
(919 citation statements)
references
References 33 publications
71
821
5
12
Order By: Relevance
“…3a) and an increase in mobility when cells were cultured in FGF-1 (Figs. 3d and e) also support evidence by others that EMT can be induced in vitro in primary tumor cells [25,26]. The expression of Zeb1, Zeb2, Snail and Slug have all been implicated in EMT induction and the acquisition of an invasive cell phenotype, as reviewed in [24].…”
Section: Discussionsupporting
confidence: 76%
“…3a) and an increase in mobility when cells were cultured in FGF-1 (Figs. 3d and e) also support evidence by others that EMT can be induced in vitro in primary tumor cells [25,26]. The expression of Zeb1, Zeb2, Snail and Slug have all been implicated in EMT induction and the acquisition of an invasive cell phenotype, as reviewed in [24].…”
Section: Discussionsupporting
confidence: 76%
“…TMPRSS4 overexpression induces an EMT associated with SIP1/ZEB2 induction and E-cadherin loss in SW480 cells Because loss and/or reduction of E-cadherin expression correlates positively with tumor cell invasion and metastasis and is a key hallmark of EMT (Thiery, 2002;Thiery and Sleeman, 2006), regulation of E-cadherin in cells overexpressing TMPRSS4 was assessed. Consistent with reports from other groups (Brabletz et al, 2001;Conacci-Sorrell et al, 2003), we found that expression of E-cadherin in SW480 cells (data not shown) and the vector transfectant (Figure 5b) was induced with increasing cell confluency. However, E-cadherin expression was markedly reduced in T17 and T4 cells at both the mRNA and protein levels (Figure 5b) when compared with the vector transfectant, regardless of whether cells were seeded and grown for 2 days in sparse culture (5 Â 10 3 cells cm À2 ) or at confluency (8 Â 10 4 cells cm À2 ).…”
Section: Tmprss4 Promotes Invasion Metastasis and Emt H Jung Et Alsupporting
confidence: 92%
“…As for CDH1 expression, we observed in an earlier study that the quantification of CDH1 RNA in the whole biopsy is a good marker of E-cadherin expression and that non-significant intra-tumor differences were found in E-cadherin staining (Pena et al, 2005), in contrast with other authors' findings (Brabletz et al, 2001).…”
Section: Adh-gfp Adh-sn Row Column Cytokine Cytokinefull Name Medianmentioning
confidence: 62%